القراءات القرآنية وصلتها بالأحرف السبعة - عوض سامي; عبد الرحيم خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
إن حديث رسول الله – صلى الله عليه وسلم -: " إن هذا القرآن أنزل على سبعة أحرف " واختيار ابن مجاهد للقراءات السبع أشكل على كثير من الناس، فظنوا أن القراءات السبع تمثل الأحرف السبعة التي نزل بها القرآن الكريم، وهذا خطأ، وما ذاك إلا من باب المصادفة، ولم يكن عن قصدٍ مسبق أو نية مبيتة ، والدليل على ذلك أن العلماء من بعد ابن مجاهد قد زادوا على تلك القراءات السبع ، فجعلوها عشر قراءات ، وقدموا بعض أصحابها على ما اختاره ابن مجاهد . القراءات العشر المتواترة عن رسول الله – صلى الله عليه وسلم – تمثل حرفاً واحداً من الحروف السبعة التي نزل بها القرآن الكريم، وهي توافق العرضة الأخيرة التي كتب عليها عثمان بن عفان – رضي الله عنه – المصاحف التي أرسلها إلى الأمصار. ويبين البحث حقيقة القرآن والقراءات، وآراء العلماء في ذلك، وبيان أن القرآن والقراءات حقيقتان بمعنى واحد. ويتطرق البحث لبيان تأثر الرسم العثماني بالحركة اللغوية والنحوية في ذلك العصر، فقد تبين أن رسم المصحف لم يتأثر بالحركة اللغوية والنحوية، لأن القراءة سنة متبعة، تؤخذ بالتواتر عن القرّاء حتى تصل بالسند إلى رسول الله – صلى الله عليه وسلم -. فالرسم العثماني يشير إلى ما في الكلمة من قراءات، وإظهار لغات العرب، وكل ذلك توقيف من النبي عليه السلام ، فهو من أمر بكتابة المصحف فور نزوله ، وأمر الصحابة بعدم كتابة الحديث الشريف لكي لا يختلط بالقرآن الكريم. ويبين البحث فوائد تعدد القراءات، وما في ذلك من جماليات وإعجاز القرآن الكريم. ويتناول تعريف القراءات، وأركانها الصحيحة، وأنواعها من حيث السند. Ibn- Mujahed’s selection of the seven letters expressed in the speech of the God’s Prophet : This Quraan was “ sent by means of seven letters ”, caused misunderstanding to many people. They thought that the seven readings represented the seven letters, which the Holy Quraan had procured. but that was a mistake of understanding. That was a kind of mere coincidence and it was not made by previous intention or a pre-made one. Observing that some readings experts (philologists) had added three more readings, so the different readings became ten. Then those philologists preferred the added readings to what had been selected by Ibn- Mujahed . The ten readings which had been conveyed about the God’s Prophet represented one letter only out of the seven letters of the Holy Quraan. That reading agreed with the last reading in which Othman Ibn- Affan had written the Quraan, and which he had sent to the different countries . Our research clarifies the reality of the readings and the Holy Quraan, and the seientists views in this coneern. Then it clarifies that the Quraan and the readings are one fact that had one meaning. The research finds the influence of the lingual and grammatical situation in that era, upon the Othmani’s drawings, because the reading is an ever followed “ Senneh ” which is taken consequently from readers one after the other, till it reached the God’s Prophet . The Othmani’s drawing refered to the different meanings of one word, and manifested the Arab’s colloquials which was a kind of inevitable / order made by our Prophet : Ordered to write down the Quraan as soon as it was inspired and sent, then he ordered his fellows not to write down his speech so as not to mix with the Quraan speech Our research states the different advantages of the different readings which contain man myths and beauties of the Holy Quraan. Then it handles the definition of readings and their correct rules and their different sorts by means of reference .